2022
DOI: 10.1155/2022/4915887
|View full text |Cite
|
Sign up to set email alerts
|

Association of Red Cell Distribution Width-to-Platelet Ratio and Mortality in Patients with Sepsis

Abstract: Background. As a novel inflammatory index, the ratio of red cell distribution width (RDW) to platelet count (RPR) may have prognostic value in some critical illnesses. However, studies on the prognostic influence of RPR in patients with sepsis are few. This study is aimed at investigating the association between RPR levels and 28-day mortality in patients with sepsis. Methods. Data of patients with sepsis were obtained from the Medical Information Mart for Intensive Care III database. The best cut-off value wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…5 (9), a017863. doi:10.1101/cshperspect.a017863 Shang, W. J., Jing, W. Z., Wang, Y. P., Kang, L. Y., Du, M., Liu, J., et al (2022). Epidemic situation of multidrug-resistant tuberculosis and change trend in Belt and Road countries.…”
Section: Discussionmentioning
confidence: 99%
“…5 (9), a017863. doi:10.1101/cshperspect.a017863 Shang, W. J., Jing, W. Z., Wang, Y. P., Kang, L. Y., Du, M., Liu, J., et al (2022). Epidemic situation of multidrug-resistant tuberculosis and change trend in Belt and Road countries.…”
Section: Discussionmentioning
confidence: 99%
“…Low ALB concentration is correlated with the higher risk of mortality in patients with diabetic ketoacidosis [ 35 ]. Existing evidence has shown the more accuracy of combined inflammation-related indexes to predict the mortality [ 36 , 37 ]. Previous studies have shown that RAR was positively associated with the all-cause mortality of patients with diabetic complications [ 7 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Kaplan-Meier (KM) method was applied to draw survival curves for in-hospital mortality and a log-rank test was conducted to determine the difference between the two groups. Cox proportional hazard models with hazard ratios (HRs) and 95% confidence intervals (CIs) were used to assess the effect of thiamine use on prognosis by adjusting various confounders, including demographic features, comorbidities, scoring systems, vital signs, laboratory tests, and clinical therapy ( Liu et al, 2022 ). Potential multicollinearity among variables was tested using the variance inflation factor (VIF), with a VIF ≥5, indicating the presence of multicollinearity.…”
Section: Methodsmentioning
confidence: 99%